2021
DOI: 10.3390/su13020956
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Utilization in Microalgae: A Sustainable Method for Wastewater Treatment

Abstract: In plant cells, ammonium is considered the most convenient nitrogen source for cell metabolism. However, despite ammonium being the preferred N form for microalgae, at higher concentrations, it can be toxic, and can cause growth inhibition. Microalgae’s tolerance to ammonium depends on the species, with various taxa showing different thresholds of tolerability and symptoms of toxicity. In the environment, ammonium at high concentrations represents a dangerous pollutant. It can affect water quality, causing num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 121 publications
2
55
0
3
Order By: Relevance
“…platensis culture medium, as well [41]. According to the current research, chlorophyll-a content decreased with increasing theurea concentration.…”
Section: Statistical Analysis and Experimental Designsupporting
confidence: 63%
See 1 more Smart Citation
“…platensis culture medium, as well [41]. According to the current research, chlorophyll-a content decreased with increasing theurea concentration.…”
Section: Statistical Analysis and Experimental Designsupporting
confidence: 63%
“…Moreover, urea contains two nitrogen atoms in a molecule with more than 45% of nitrogen while standard Zarrouk's medium was containing 16% of the nitrogen in sodium nitrate [40]. Abd El-Baky [41] found that nitrogen concentration reduction in S. platensis culture decreases phycocyanin, chlorophyll and protein contents due to breaking down the chloroplasts. The concentration of chlorophyll increased when nitrogen was used in the S.…”
Section: Statistical Analysis and Experimental Designmentioning
confidence: 99%
“…in Arthrospira cultures [52,64], especially when combined with low CO 2 supply and renewal of aliquots of the culture with fresh medium [52], as performed here at each harvesting time during the F experiment (see Section 2.2). Repeated batch addition of NH 4 + is also a very helpful strategy in the treatment of Chlorella and other phototrophs [19,52], and also of contaminant protozoans, due to the predominance of the toxic NH 3 over NH 4 + at high pH values (>9.26 at 25 • C; [65,66]). In this study, removal of Schmidingerothrix was observed the day after the first treatment with ammonium sulphate (Table A3, Appendix B), indicating the sensitivity of this ciliate with respect to ammonia at the dosed amount.…”
Section: Microzooplankton and Phototrophs Dynamics And Culture Treatmentmentioning
confidence: 99%
“…Industrial wastewater, agricultural activities, and municipal effluents increase the ammonia nitrogen discharges into environmental resources [ 7 ]. Ammonium pollution affects the aquatic quality of water bodies, resulting in severe environmental problems such as pH shift, cyanotoxin creation, oxygen reduction, eutrophication of downstream liquids, enhanced eutrophication of rivers and lakes, and exhaustion of dissolved oxygen, being toxic aquatic animals at a level greater than 1.9 mg·L −1 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microalgae have been discussed as a valuable feedstock for many applications, including biofuel production [ 14 , 15 ]. It was calculated that roughly 40–100 kg of inorganic nitrogen compounds and 11–13 ML/Ha/year of water are required for 1 ton of microalgal growth [ 8 ]. It was also anticipated that roughly 2500 m 3 of wastewater might be processed to produce 1 ton of microalgal biomass [ 16 ].…”
Section: Introductionmentioning
confidence: 99%